Mémoires de l'émancipation : côte kényane, XIXe-XXe siècles - Abungu, Patrick; Ballarin, Marie Pierre; Nyanchoge, Samuel (Les mondes de l'esclavage: une histoire comparée, 2021)
Keywords: Esclavage -- Zanzibar

Traces of Clay: Exploring Slave and Migrant Identities in Medieval Swahili Zanzibar - Rødland, Henriette (Cambridge Archaeological Journal, 2025)
Abstract The East African coast has long been recognized as a cosmopolitan region, where different cultures and peoples met and exchanged ideas, goods and knowledge. The culture that developed there from the seventh century ce was shaped by these relations, often referred to under the term Swahili, and many of the coastal residents engaged in Islamic practice, long-distance trade, conspicuous consumption of valued goods, and spoke a common language. This paper investigates the presence of slaves and migrants from the East African interior, through pottery assemblages uncovered at two eleventh- to fifteenth-century ce sites in northern Zanzibar: Tumbatu and Mkokotoni. These are groups of people not usually discussed in relation to medieval Swahili towns, and slavery has been especially difficult to study archaeologically on the coast. Through a material culture of difference, I argue that enslaved and non-elite migrants can be recognized and allow for a fuller understanding of socio-economic and cultural complexity in Swahili towns.
Keywords: Esclavage -- Zanzibar

En quête d'autonomie: Un couple de rachetés dans la mission catholique de Bagamoyo, Tanzanie (1890-1920) - Nivière, Adèle (Revue d'histoire contemporaine de l'Afrique, 2025)
Bagamoyo, ville de la côte swahilie en Tanzanie actuelle, a été un point névralgique de la traite des esclaves en Afrique de l’Est du xixe siècle au début du xxe siècle. Dans ce contexte, les missionnaires catholiques ont racheté de nombreux esclaves pour les convertir. Une fois mariés, ces anciens esclaves étaient installés dans des villages chrétiens. Cet article retrace la trajectoire d’un de ces couples, à l’échelle individuelle, à travers l’éclairage des registres paroissiaux. Ces archives se révèlent utiles pour retracer les parcours d’émancipation, en particulier du point de vue de la famille, domaine central de la politique missionnaire. Le jeune couple navigue dès lors, en fonction d’opportunités genrées, entre l’insertion dans une communauté affective et religieuse chrétienne, et les réseaux économiques d’appartenance alternatifs offerts dans les villes de la côte swahilie, en dehors du cadre de la mission.
Keywords: Esclavage -- Zanzibar

The Blockade of Zanzibar (1888-1889). The Anglo-German-Portuguese fleet in the fight against east-African slave trade - Saldanha, Nuno (War@sea: Science and Technology, 2024)
Keywords: Esclavage -- Zanzibar

God's Laborers: Missionary Work and Imperialism in the Congo From 1878-1908 - Peterson, Ana (Utah State university, 2024)
In 1878, Henry Craven opened the first Protestant mission in the Congo. The Livingstone Inland Mission created multiple stations along the Congo River to reach the interior. It stayed active for six years before transferring its stations to Swedish and American missions. Five years after its closure, a sister mission, the Congo Balolo Mission, resumed efforts to teach the people living in the interior. This thesis explores the evolving reaction of the missionaries to state violence. It argues that these missionaries initially supported imperial violence that enforced laws that aligned with their beliefs, such as removing the slave trade. Once that violence extended to profits alone and increased in violence, the missionaries joined the movement to improve conditions in the Congo.
Keywords: Esclavage -- Zanzibar; Tippo Tip (1837-1905)

“I Authored This Book in the Absence of My Slave”: Enslaved East Africans and the Production of Occult Knowledge across the Omani Empire - AlMaazmi, Ahmed Yaqoub (Monsoon, 2024)
What role did enslaved East Africans play in producing and transmitting the occult sciences between East Africa and Oman? This article explores the relationship between enslaved East Africans and the occult sciences in the works of Nās.ir bin Abī Nabhān (1778–1846), a jurist and practitioner of the occult sciences who lived between Oman and East Africa. It argues that enslaved East Africans were instrumental in producing and disseminating valuable occult knowledge. The analysis informs how occult knowledge operated and circulated between the Arabian and African coasts, animated in occultist idioms, and was written in Arabic and Swahili. Moreover, it explores how East African and Omani actors articulated occultist knowledge by paying attention to the interlinkages between power dynamics and knowledge hierarchies during the expansion of the Bu Saidi Empire in the nineteenth century. This study explores uncharted waters in a transoceanic sphere by tracing translation processes and nonEuropean imperial knowledge production in the Indian Ocean world.
Keywords: Esclavage -- Zanzibar; Occultisme -- Oman

An Abolitionist Vicious Circle: Slaving, Antislavery, and Violence on the Shores of Lake Tanganyika at the Onset of Colonial Occupation - Rossi, Benedetta (Slavery & Abolition, 2024)
In the late nineteenth century, abolitionists felt entitled to use all possible means to save the African victims of the slave trade. As European imperialism rose, abolitionism legitimized interventionism. This article explores how a major humanitarian movement could sanction colonial occupation and the violence that accompanied it. It also examines the position of African slaveholders who resisted the entrenchment of European rule and defended an order in which slavery was common. It focuses on two main actors: French Captain Leopold Joubert, Catholic royalist and former pontifical Zouave who supported Cardinal Lavigerie's Missionaries of Africa and Belgian King Leopold II's allegedly abolitionist endeavours; and Tippu Tip, a trader and slaver who, like Joubert, worked for self-styled abolitionists such as Leopold II and the Sultan of Zanzibar. The connected microhistories of these men show how the international problematization of African slavery fuelled both European imperialism and anti-colonial resistance, while also creating circumstances in which enslaved persons emancipated themselves. The article investigates the moral perceptions of individuals whose sense of self was predicated upon values embodied by Europe's monarchies, the papacy of Rome, and the sultanate of Zanzibar. Faced with what they perceived as existential threats to these institutions, they responded with rising radicalism.
Keywords: Esclavage -- Zanzibar; Tippo Tip (1837-1905)

Intervention d'humanité: la répression de la traite des esclaves à Zanzibar années 1860-1900 - Cheriau, Raphaël (CNRS éditions, 2023)
Keywords: Esclavage -- Zanzibar

Notices relatives à l'État indépendant du Congo et projets antérieurs ([1876-1884] 1885-1908) - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Belgique, Congo, Rwanda et Burundi : Guide des sources de l'histoire de la colonisation (19e-20e siècle), 2021)
Keywords: Archives -- Bruxelles; Esclavage -- Oman; Esclavage -- Zanzibar; Relations -- Oman -- Belgique; Tippo Tip (1837-1905)

Notices relatives à la Belgique et aux territoires sous autorité belge : Congo, Ruanda Et Urundi ([1884]1909-1960/1962) - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Belgique, Congo, Rwanda et Burundi : Guide des sources de l'histoire de la colonisation (19e-20e siècle), 2021)
Keywords: Archives -- Bruxelles; Esclavage -- Oman; Esclavage -- Zanzibar; Relations -- Oman -- Belgique; Tippo Tip (1837-1905)

Belgique, Congo, Rwanda et Burundi : Guide des sources de l’histoire de la colonisation (19e-20e siècle): Vers un patrimoine mieux partagé ! - Tallier, Pierre-Alain; Van Eeckenrode, Marie; Van Schuylenbergh, Patricia (Brepols Publishers, 2021)
Vaste question que celle des sources relatives à la colonisation belge en Afrique ! Alors que chercheurs et société civile réclament un (meilleur) accès aux « archives coloniales », il n’existait jusqu’ici aucun outil permettant d’identifier et de localiser toutes les sources disponibles en Belgique. Pourtant, ce sont près de 20 kilomètres linéaires d’archives relatives à la colonisation qui reposent dans plus de 80 institutions de conservation en Belgique. La rédaction du « Guide des sources de l’histoire de la colonisation (belge) » constitue donc une avancée cruciale dans l’identification et la description des archives relatives à l’État indépendant du Congo (1885-1908), au Congo belge (1908-1960) et au Ruanda-Urundi ([1916] 1923-1962) : archives produites par les souverains et les différents gouvernements, par les hommes et femmes politiques, par l’administration coloniale, par les entreprises, les missions religieuses, les universités, les fondations, le monde associatif et culturel et tous les autres acteurs de cette histoire dont les Africains bien évidemment. Sorte de GPS des archives coloniales, ce guide permet pour la première fois au citoyen et au chercheur, peu importe le continent sur lequel il vit, de savoir précisément qui conserve quoi sur le territoire belge. Il répond à une triple nécessité : scientifique, sociétale et mémorielle. Riche de plus de 1500 notices pour près de 2300 pages, cette publication propose une description sommaire et une remise en contexte de tous les fonds et collections d’archives coloniales conservés en Belgique, leur intérêt pour la recherche, leurs liens avec d’autres fonds et collections, etc. Une large et indispensable introduction replace les archives relatives à la colonisation belge dans le débat international et pose les questions très sensibles du partage de patrimoine, du retour des archives en Afrique et de la construction de la mémoire. Le guide est également accompagné d’un bilan historiographique fouillé, de pistes permettant de repérer les sources relatives à la colonisation belge conservées à l’étranger ou encore d’un cahier de plusieurs centaines d’illustrations qui souligne l’intérêt et la nécessité d’élargir les champs de la recherche aux sources iconographiques.
Keywords: Archives -- Bruxelles; Esclavage -- Oman; Esclavage -- Zanzibar; Relations -- Oman -- Belgique

Le mythe de la malédiction de Cham et la côte swahili - Belhacel, Abdelhakim (2024)
Keywords: Esclavage -- Zanzibar

‘Siendi’ (I won’t go): concubines’ activism in the abolition of slavery in the Zanzibar Protectorate - McMahon, Elisabeth (Slavery & Abolition, 2020)
Keywords: Esclavage -- Zanzibar

The Sultans of Zanzibar and the Abolition of Slavery in East Africa - Liebst, Michelle (Law and History Review, 2024)
In 1890, Sultan Ali of Zanzibar declared in writing that “we wish by every means to stop the slave trade.” Statements like these, in addition to the actual passing of anti-slavery legislation, call into question the generally accepted scholarly understanding that the sultans of Zanzibar only agreed to pass and enforce anti-slavery legislation because they were under duress from European, mainly British, powers, who negotiated favorable political and economic benefits in return for (gradual) abolition. A close analysis of the sources tells a more complicated story of both collaboration and conflict between the Zanzibari sultans, their subjects, and the British agents. Moreover, each sultan had distinctive political and religious beliefs, as well as individual personal experiences and outlooks. This paper explores the anti-slavery legislation passed under three sultans of Zanzibar: Barghash bin Said (1870–1888) who prohibited the transport of slaves by sea in 1873, Ali bin Said (1890–1893) who passed the Slave Trade Prohibition Decree of 1890, and Hamoud bin Mohammed (1896–1902) who passed the Abolition Decree of 1897. By analyzing draft treaties and correspondence before and after the passing of legislation, this paper argues that the sultans and their advisors were not devoid of ideological interest in ending slavery; and that British agents and explorers in the region were too hastily hailed as abolitionists.
Keywords: Esclavage -- Zanzibar

زنجبار التكالب الإستعماري وتجارة الرق - الإسماعيلي, عيسى بن ناصر (مكتبة الجيل الواعد, 2023)
Keywords: Esclavage -- Zanzibar